Low‐Cost, Low‐Power, High‐Capacity 3R OEO‐Type Reach Extender for a Long‐Reach TDMA‐PON - Kim, Kwangok; Lee, JieHyun; Lee, Sangsoo; Lee, Jonghyun; Jang, Younseon (ETRI journal, 2012)
This paper proposes a low‐cost, low‐power, and high‐capacity optical‐electrical‐optical‐type reach extender that can provide 3R frame regeneration and remote management to increase the reach and split ratio with no change to a legacy time division multiple access passive optical network. To provide remote management, the extender gathers information regarding optical transceivers and link status per port and then transmits to a service provider using a simple network management protocol agent. The extender can also apply to an Ethernet passive optical network (E‐PON) or a gigabit‐capable PON (G‐PON) by remote control. In a G‐PON, in particular, it can provide burst mode signal retiming and burst‐to‐continuous mode conversion at the upstream path through a G‐PON transmission convergence frame adaptor. Our proposed reach extender is based on the quad‐port architecture for cost‐effective design and can accommodate both the physical reach of 60 km and the 512 split ratios in a G‐PON and the physical reach of 80 km and the 256 split ratios in an E‐PON.